Feasibility of infrared thermography use for neuromusculoskeletal rehabilitation - Postolache, G.; Postolache, O.; Martim, F. F.; Vardasca, R.; Mendes, J. (13th IEEE International Symposium on Medical Measurements and Applications, MeMeA 2018, 2018)
In this study, the feasibility of using infrared thermography (IRT) for measurements in neuromusculoskeletal rehabilitation was investigated. Research findings suggest that measurements using IRT were used for the assessment of physical exercises, face muscle activity, muscle injuries, myofascial trigger points, joints and spinal cord related disorders, rheumatoid arthritis as well as for physiotherapy monitoring. Evidence exists that IRT technique is a valid tool for using in physiotherapy process, or in different phases of neuromotor rehabilitation.